3-Dimensional Cerebral Dural Venous Sinus Anatomy and Configuration in Space. (16th November 2020) - Anand, Adrish; Crowley, Samantha; Johnson, Jeremiah N
Abstract: INTRODUCTION: The human cerebrum requires a constant influx of arterial blood flow and egression of venous flow to maintain homeostasis. The Dural venous sinuses comprise the dominant cerebral venous outflow path. Understanding the spatial configuration of the Dural venous sinuses can provide valuable insight into several pathological conditions such as venous sinus stenosis, pseudotumor cerebri, and tumors compressing the sinuses. Previously, only 2D data or cadaveric data have been used to understand cerebral outflow. Recently, 3D rotational venography (3D-RV) has provided the means to visualize the venous outflow with high quality 3D images. METHODS: Patients who underwent a 3D-RV procedure were identified by reviewing the Baylor St. Luke's Medical Center endovascular database. Patients were further filtered on the criteria that the angiographic images were of high quality and clearly depicted the venous outflow from the torcula to the internal jugular vein. Patient related factors and indications for the studies were documented. Post-torcula venous sinuses were divided into segments. Segment length, sinus displacement in 3-dimensional space, and cross-sectional area were measured for all subjects. RESULTS: The transverse sinus (60.2 mm) was the longest segment, followed by the sigmoid sinus (55.1 mm). Cross sectional area was least at the middle of the transverse sinus (21.3 mm 2 ), but gradually increased at the sigmoid sinus (33.547 mm2), and drastically increased at the jugular bulb (49.7 mm 2 ). The only variation in displacements of venous flow was at the sigmoid-jugular junction, where 55% of cases had lateral displacements versus 45% medial, and 78% were superior versus 22% inferior. CONCLUSION: 3D-RV reconstructions provide highly precise data on the anatomy of the cerebral venous Dural outflow. Understanding the anatomy and spatial configuration of the main venous outflow of the brain is the first step in characterizing the dynamic nature of cerebral venous outflow in different postural positions and pathological conditions.